The Current Occurrences of Inequality: Formation Catechist for Awareness of Significant Moral Values - Naibaho, Megawati (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research has been developed around the two contrasting views/themes of current occurrences of inequality and significance for formation catechist. The are several problems that occur in society, especially the absence of appreciation of Catholic moral values, require the development of faith and character for society, especially for Catholics. In reality, especially in pastoral circumstances, the management of community development through activities can contribute to overcome the problem by providing opportunities for lay people to become a catechist. Hence, identifying problems of injustice is important because everybody is members of families and communities who sometimes experience injustice. If this injustice is not addressed properly, it will be impossible for a catechist to carry out his duties conscientiously and dedicatedly for the common good. The method used in this research is comparative research. Through this method, the researcher tries to gather data and process data more flexibly by using a qualitative or quantitative approach. Thus, it is hoped that the research results will be able to reveal a significant relationship between inequality and the formation catechists as ministers in the Church.